Running a history programme outside the classroom: a case study of athletics at Zonnebloem College (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Sport history has been neglected, even ignored, in South African classroom and pedagogy debates. Despite, a large reservoir of South African sport history literature of a formal and informal nature being available for teachers, other historical areas of concern are usually focussed on. This study attempts to break this mould and offer history teachers an opportunity for creating pedagogical opportunities outside the formal history curriculum. In order to achieve this, a history of athletics at the Zonnebloem College during the 19th and early 20th centuries was researched. A brief literature overview of previous research on Zonnebloem history is presented as background material. The study is then introduced with a historical oversight of school athletics in 19th century England. Next, the historical development of sport during the 19th century at Zonnebloem is explored. The crux of the historical account hones in on the history of athletics at Zonnebloem during the 19th and early 20th centuries. Finally, the article is concluded by presenting teachers with pedagogical opportunities outside the classroom through the interrogation of historical sources, all of which are taken from the Zonnebloem historical narrative.
Keywords: Athletics; Colonial education; Muscular Christianity; Pedagogical opportunities; Zonnebloem College; Sport history